(untitled) (The Journal of Geography Education in Africa, 2021)
South Africa is one of only a few countries that has Geographic Information Systems (GIS) in the secondary school curriculum. Of these few, SA is even more singular as its Geography syllabus includes GIS geoprocessing. Results from this study show that only a minority of teachers teach practical GIS classes irrespective of their Examination Board, access to hardware, how resourced their school is or whether they teach at a private or a government school. The key determinants to teaching practical GIS lessons are the teacher’s perceived GIS expertise and access to spatial data and time. Software, connectivity, and power supply are also identified as challenges. Teachers who participated in the study overwhelming agree that there are numerous benefits to using GIS in the classroom. They also expressed a keen willingness to attend GIS courses and learn more about QGIS. A sample group evaluated how OpenStreetMap (OSM) could be used to create local spatial data and how QGIS can be used to teach the GIS curriculum and used to map local data for individual research projects. There is an urgent need for more current research, both globally and locally, into how GIS can be used more in secondary school pedagogy.